The language of pain: A short study - Arun Rathnam; Nidhi Madan; Neeti Madan (Contemporary Clinical Dentistry, 2010)
Background: Pain perception is a very controversial topic in child patients. It is affected by various factors such as fear, anxiety, previous experiences, parental factors, and pain threshold. The communication of such pain by the child to the parent is also very confusing with children having rudimentary and developing communication skills. A study to evaluate the pain perception of children and the parental understanding of the children′s pain would be helpful in this scenario. The effect on behavior due to pain is also attempted in this particular study. Materials and Methods: A cross-sectional study of 100 children aged between 5-13 years accompanied by either parent was performed. Data collection was done with the help of questionnaires, which assessed the parental understanding of the child′s pain. Pain perception recording was done with the Visual Analog Scale of Faces (VASOF). The behavior of the child was noted using the Frankl′s behavior rating scale. Data was collated and statistical analysis was performed using the SPSS (version 10) software. Results and conclusion: The results show that parental factors such as education, work culture, influence parental understanding of pain. VASOF proves to be a reliable tool for pain perception in children. Behavior of the child shows a positive correlation to pain perception.